2011
DOI: 10.1016/j.envpol.2010.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Responses of evergreen and deciduous Quercus species to enhanced ozone levels

Abstract: t r a c tPlants of one evergreen oak (Quercus ilex) and three deciduous oaks (Q. faginea, with small leaves; Q. pyrenaica and Q. robur, with large leaves) were exposed both to filtered air and to enhanced ozone levels in Open-Top Chambers. Q. faginea and Q. pyrenaica were studied for the first time. Based on visible injury, gas exchange, chlorophyll content and biomass responses, Q. pyrenaica was the most sensitive species, and Q. ilex was the most tolerant, followed by Q. faginea. Functional leaf traits of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 43 publications
7
58
1
Order By: Relevance
“…Numerous studies have shown ozone-induced tree damage, including photosynthesis decrease (Feng et al, 2008b;Pina and Moraes, 2010;Wittig et al, 2007;Zhang et al, 2012), chlorophyll degradation (Calatayud et al, 2011;Zhang et al, 2014) and biomass reduction (Gerosa et al, 2015;Hu et al, 2015;Wittig et al, 2009). In this study, ozone had significant effects on A sat , PhiPS2, chlorophyll content and LMA, which were also significantly different at different times and different clones.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Numerous studies have shown ozone-induced tree damage, including photosynthesis decrease (Feng et al, 2008b;Pina and Moraes, 2010;Wittig et al, 2007;Zhang et al, 2012), chlorophyll degradation (Calatayud et al, 2011;Zhang et al, 2014) and biomass reduction (Gerosa et al, 2015;Hu et al, 2015;Wittig et al, 2009). In this study, ozone had significant effects on A sat , PhiPS2, chlorophyll content and LMA, which were also significantly different at different times and different clones.…”
Section: Discussionmentioning
confidence: 53%
“…4). Over the past decade there has been a lot of research on plant sensitivity to ozone, including studies comparing the sensitivity of evergreen and deciduous species (Calatayud et al, 2011(Calatayud et al, , 2010, the sensitivity of urban tree species (Li et al, 2016;Xu et al, 2015) and the sensitivity of different poplar genotypes (Di Baccio et al, 2014;Dumont et al, 2014). Li et al (2016) found that ozone sensitivity was strongly related to LMA, and leaves with lower LMA are more sensitive to ozone (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, Viburnum lantana and Hybiscus syriacus, two species that were fumigated in parallel with L. dianae in the year 2005 and that are considered as being very sensitive to ozone (Paoletti et al, 2009;Calatayud et al, 2010), developed symptoms later and less extensively. Amphystomatous leaf type, relatively large substomatic chambers and abundant intercellular spaces are anatomical features that reduce leaf resistance to gas exchange and therefore favor ozone diffusion inside the leaves (Lyons et al, 2000;Calatayud et al, 2011). Species with relatively high stomatal conductance, as is the case of Lamottea, might be more susceptible to the detrimental effects of oxidants, including more visible injury and impaired CO 2 assimilation (Reich, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of detrimental changes at the biochemical, physiological and molecular levels have been demonstrated in conifers and deciduous trees (Koch et al, 1998;Kopper and Lindroth, 2003;Richet et al, 2011Richet et al, , 2012Zhang et al, 2014a). Experimental evidence indicates that not only species but also cultivars, genotypes and clones, show different sensitivity to O 3 (Calatayud et al, 2011;Castagna et al, 2015;Dumont et al, 2014;H€ aiki€ o, 2009;Paoletti and Grulke, 2010;Zhang et al, 2012Zhang et al, , 2014c.…”
Section: Introductionmentioning
confidence: 99%